The Effect Of Variations In The Concentration Of Ethanol Extract Of Green Okra Fruit (Abelmoschus Esculentus L. Moench) On The Antioxidant Activity Of Face Mist Preparations Using The DPPH Method - Sirna Dzawil Kamala; Alfina Nurrahman; Kharisma Jayak Pratama (International Journal of Health Engineering and Technology, 2026)
Skin aging due to oxidative stress from free radicals from UV exposure and pollution requires natural antioxidants in topical products. Ethanol extract from green okra fruit (Abelmoschus esculentus L. Moench) rich in phenolics has strong potential to capture DPPH. This quantitative preclinical experimental study aims to test the effect of extract concentration (3%, 6%, 9%) on antioxidant activity and physical quality of face mist preparations. The population of face mist preparations; purposive samples include controls and three formulas with three replications. UV-Vis spectrophotometer instruments for IC50 DPPH at 516 nm (operating time 15 minutes), pH meter, Brookfield viscometer. Descriptive and inferential analysis One-Way ANOVA and Tukey HSD (SPSS, p <0.05). The results showed IC50: control 71.92 ppm (strong), Formula I 146.75 ppm (moderate), II 80.63 ppm (strong), III 78.72 ppm (strong); pH 4.57-5.15 (skin compatible); viscosity 1.22-3.75 mPa.s (meets <5 mPa.s); homogeneous. High concentrations significantly increase antioxidant activity (p<0.05). In conclusion, the 9% formula of optimized strong antioxidant face mist meets cosmetic standards, with anti-aging potential.